2017
DOI: 10.1017/s095026881700228x
|View full text |Cite
|
Sign up to set email alerts
|

A spatial and temporal analysis of paediatric central nervous system infections from 2005 to 2015 in Ho Chi Minh City, Vietnam

Abstract: Central nervous system infections (CNSI) are a leading cause of death and long-term disability in children. Using ICD-10 data from 2005 to 2015 from three central hospitals in Ho Chi Minh City (HCMC), Vietnam, we exploited generalized additive mixed models (GAMM) to examine the spatial-temporal distribution and spatial and climatic risk factors of paediatric CNSI, excluding tuberculous meningitis, in this setting. From 2005 to 2015, there were 9469 cases of paediatric CNSI; 33% were ⩽1 year old at admission an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…A similar spatial pattern was described from an epidemiological analysis of CNS infections among children admitted to Ho Chi Minh City hospitals in Vietnam – with most patients coming from districts near the hospital [18]. While the majority of infections (55%) in the Vietnam study were presumed to be bacterial in origin, in this study from Lao PDR bacterial infections were identified in only 38% (170 out of 450 patients with diagnoses).…”
Section: Discussionsupporting
confidence: 78%
“…A similar spatial pattern was described from an epidemiological analysis of CNS infections among children admitted to Ho Chi Minh City hospitals in Vietnam – with most patients coming from districts near the hospital [18]. While the majority of infections (55%) in the Vietnam study were presumed to be bacterial in origin, in this study from Lao PDR bacterial infections were identified in only 38% (170 out of 450 patients with diagnoses).…”
Section: Discussionsupporting
confidence: 78%
“…A similar spatial pattern was described from an epidemiological analysis of CNS infections among children admitted to Ho Chi Minh City hospitals in Vietnam-with most patients coming from districts near the hospital [21]. While the majority of infections (55%) in the Vietnam study were presumed to be bacterial in origin, in this study from Lao PDR bacterial infections were identified in only 38% (170 out of 450 patients with diagnoses).…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 81%
“…are increasingly recognized as important causes [9]. Detailed analyses that confirm the cause of CNS related infections or assess their spatial and temporal distribution in the region are rare [10][11][12][13]. Several CNS infections are vaccine preventable, however high costs of some vaccines, and geographic accessibility can limit their reach.…”
Section: Introductionmentioning
confidence: 99%
“… 43 , 110 , 128 , 130 , 131 The heterogeneity of the effects of rainfalls on hand-foot-mouth disease was higher than that of temperatures or humidity. 132 Other IDs such as children's nervous system infection, 134 plague, 135 AIDS-associated Penicillium marneffei infection, 136 or rabies 130 were only mentioned in a few studies with insufficient information on climate-infectious disease association.…”
Section: Resultsmentioning
confidence: 99%